Use alone or in Combination of Red and Infrared Laser in Skin Wounds - de Lima, Fernando José Camello; Barbosa, Fabiano Timbó; de Sousa-Rodrigues, Célio Fernando (Journal of Lasers in Medical Sciences, 2014)
A systematic review was conducted covering the action of red laser, infrared and combination of both, with emphasis on cutaneous wound therapy, showing the different settings on parameters such as fluency, power, energy density, time of application, frequency mode and even the type of low-power lasers and their wavelengths. It was observed that in general, the lasers brings good clinical and histological results mainly, but there is not a protocol that defines a dosage of use that has predictability of therapeutic success in repairing these wounds.